MPARATIVE REPRODUCTIVE PERFORMANCE OF CAPTIVEREARED INDIAN STOCKS OF FENNEROPENAEUS MERGUIENSIS (DE MAN) WITH WILD-CAUGHT BROODSTOCK - WAIKHOM, GUSHEINZED; PILLAI, S. M. (Journal of the Inland Fisheries Society of India, 2021)
The potential for domestication of Fenneropenaeus merguiensis through closed life-cycle production and reproductive performance of the pond reared domesticated first generation broodstock were compared with wildcaught broodstock over a period of 8 weeks reproductive performance trial. There was significant variation (P<0.05) in reproductive performance between wild-caught and two pond reared lines of the F. merguiensis broodstock. However, the lower reproductive performance found in the pond-reared spawners did not prevent closed-cycle production and demonstrated a level of reproductive output sufficient for commercial scale hatchery seed production. Key words: Fenneropenaeus merguiensis; wild broodstock; pond-reared broodstock; reproductive performance.